PERENCANAAN KAWASAN BOROBUDUR SEBAGAI DAERAH TUJUAN WISATA - Hadi Sukarno, Teguh (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
ideally. there are at least three parties involved in planning a tourism area namely: government, tourism industries, and the local community with their interests. A tourism destination has to meet some criteria to be successful: aspects of organizational and marketing planning, product aspects, the asÂpects of quality planning. Tourism development initiated with good planning is expected to give a beneficial impact on the local industry, government, and community. A good tourism planning will take into consideration in the very beginning all the possible impacts, positive or negative so that all measures can be planned in advance to anticipate them. This article overviews the planÂning of Borobudur as a Tourism Destination.